2006
DOI: 10.1210/me.2006-0168
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Induction of Glial Cell Proliferation and Axonal Outgrowth and Myelination by Brain-Derived Neurotrophic Factor

Abstract: Brain-derived neurotrophic factor (BDNF) belongs to the neurotrophin family of neuronal cell survival and differentiation factors but is thought to be involved in neuronal cell proliferation and myelination as well. To explore the role of BDNF in vivo, we employed the intermediate pituitary melanotrope cells of the amphibian Xenopus laevis as a model system. These cells mediate background adaptation of the animal by producing high levels of the prohormone proopiomelanocortin (POMC) when the animal is black ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…OPC numbers then dropped to a significantly lower number than that seen on NsAs. These data suggest that OECs secrete an OPC mitogen(s) (de Groot et al, 2006;Lipson et al, 2003). The production and survival of oligodendrocytes is regulated by axonal signals (Barres and Raff, 1994;Simons and Trajkovic, 2006;Trapp et al, 1997), and it is therefore possible that the decrease observed in the number of OPCs between Days 16 and 24 in culture was because of the death of OPCs as a result of insufficient axonal signals.…”
Section: Discussionmentioning
confidence: 92%
“…OPC numbers then dropped to a significantly lower number than that seen on NsAs. These data suggest that OECs secrete an OPC mitogen(s) (de Groot et al, 2006;Lipson et al, 2003). The production and survival of oligodendrocytes is regulated by axonal signals (Barres and Raff, 1994;Simons and Trajkovic, 2006;Trapp et al, 1997), and it is therefore possible that the decrease observed in the number of OPCs between Days 16 and 24 in culture was because of the death of OPCs as a result of insufficient axonal signals.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, in agreement with previous findings in the spinal cord , progesterone markedly stimulated BDNF mRNA in the hippocampus. This effect may be crucial for some BDNF‐regulated functions of hippocampus, including synaptic transmission, neuronal survival, dendritic spine plasticity and long‐term potentiation . The diminished BDNF mRNA in the hippocampus of untreated Wobblers may be the consequence of the ongoing neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[2] have previously reported. BDNF has been reported to have a regulation in axon myelination and regeneration, neuronal survival, axonal outgrowth, differentiation and glial cell proliferation [31][33]. BDNF is initially elevated before myelination and has been shown to modulated neuron-glia interactions in PNS and CNS [34], [35].…”
Section: Discussionmentioning
confidence: 99%